Microfinance, Poverty Alleviation and Sustainability: Towards a New Micro-Finance Model for Zimbabwe - Mago, Stephen (Journal of Economics and Behavioral Studies, 2014)
The main aim of this paper is to propose the development of a new microfinance model that can approximate sustainability in Zimbabwe. The secondary purpose is to find out whether the same model can be replicated in other developing countries. The paper adopted a mixed methodology. A crosssectional data collection method was preferred because data was collected during the time of high volatility in the country. Questionnaires, interview schedules were combined to collect data from villagers involved in microfinance programmes. Data were collected from 250 households in the Masvingo rural district area of Zimbabwe. The findings show that the two polar models are biased, hence the need for the ‘middle of the road approach’/‘hybrid model’ for the provision of microfinance services to the poor in order to achieve the twin objectives of poverty alleviation and sustainability. The paper is limited to a Masvingo district of Zimbabwe, thus replication could become a challenge. This article attempts to develop a ‘middle of the road’ model for microfinance in Zimbabwe. According to our knowledge, there is no study that has attempted to do the same.